Awakening Lazarus: Forgotten Figures — Masses and Surplus? - Kirn, Gal (Stasis, 2018)
The text aims to think through a figure largely forgotten in radical philosophy or communist theology discussions today: the Biblical figure(s) of Lazarus. The absence of this figure from current discussions might have to do with something that was pointed out by Balibar as the ongoing “fear of the masses,” and with their political awakening that is usually interpreted as violence, failure, riotous noise and absence of political program/ organization. I will perform a close reading of two stories of Lazarus from the Gospels in the first part of this article, tackling the question of the first Lazarus (from the Gospel of John) that can be seen not only as the prefiguration of the resurrection of Jesus, but also as the awakening of political “surplus” that shakes the old order and cannot be easily integrated into the new. The second Lazarus (from the Gospel of Luke) can often be seen as a somewhat stoic figure that remains outside the gates of political life and is only absolved in the afterlife. This oscillation between the figure of poor/excluded was taken up and transformed in the works of three radical thinkers: Foucault, Marx, and Fanon. A short panoramic view of the “legacy” of Lazarus shall be then explored in the second part of the article: from the early discussion of leprosy and the strategic spatial and sovereign separation of exterior and interior in Foucault and Marx’s oscillation between “surplus population” and “Lumpenproletariat,” and finally to Frantz Fanon, who predicted that political subject of Lumpenproletariat is supposed to become a spearhead of future revolutions.